Characterization of the Apelin/Elabela Receptors (APLNR) in Chickens, Turtles, and Zebrafish: Identification of a Novel Apelin-Specific Receptor in Teleosts - Zhang, Jiannan; Zhou, Yawei; Wu, Chenlei; Wan, Yiping; Fang, Chao; Li, Jing; Fang, Wenqian; Yi, Ran; Zhu, Guoqiang; Li, Juan; Wang, Yajun (Frontiers in Endocrinology, 2018)
Apelin receptor(s) (APLNR) are suggested to mediate the actions of apelin and Elabela (ELA) peptides in many physiological processes, including cardiovascular development and food intake in vertebrates. However, the functionality of APLNR has not been examined in most vertebrate groups. Here, we characterized two APLNRs (APLNR1, APLNR2) in chickens and red-eared sliders, and three APLNRs in zebrafish (APLNR2a, APLNR2b, APLNR3a), which are homologous to human APLNR. Using luciferase-reporter assays or Western blot, we demonstrated that in chickens, APLNR1 (not APLNR2) expressed in HEK293 cells was potently activated by chicken apelin-36 and ELA-32 and coupled to Gi-cAMP and MAPK/ERK signaling pathways, indicating a crucial role of APLNR1 in mediating apelin/ELA actions; in red-eared sliders, APLNR2 (not APLNR1) was potently activated by apelin-36/ELA-32, suggesting that APLNR2 may mediate apelin/ELA actions; in zebrafish, both APLNR2a and APLNR2b were potently activated by apelin-36/ELA-32 and coupled to Gi-cAMP signaling pathway, as previously proposed, whereas the novel APLNR3a was specifically and potently activated by apelin. Similarly, an apelin-specific receptor (APLNR3b) sharing 57% sequence identity with zebrafish APLNR3a was identified in Nile tilapia. Collectively, our data facilitates the uncovering of the roles of APLNR signaling in different vertebrate groups and suggests a key functional switch between APLNR1 and APLNR2/3 in mediating the actions of ELA and apelin during vertebrate evolution.